Ku oviwa ka timfanelo ta vaxinuna eka matsalwa ya mitlangu lama hlawuriweke (Abuse of men's rights in selected Xitsonga drama text) - Madalane, John (My University, 2021)
The purpose of this study is to examine the violation of men’s rights in selected Xitsonga drama texts. The study is guided by qualitative approach. The approach involves collecting and analysing non - numerical data to understand concepts, opinions or experiences. In this study purposive sampling is employed. The researcher deliberately chooses who to include in the study based on their ability to provide the necessary data. Data are collected using content and document analysis from sampled drama texts. Like other analytical methods in qualitative research methods, documents analysis requires that data be examined and interpreted in order to elicit meaning, gain understanding and develop empirical knowledge. The advantage of document analysis includes, efficiency which means that it is not time consuming but is more efficient than other research methods. Its effectiveness entails that it is less costly and makes it the method of choice. Thematic analysis is also used as the method of systematically identifying, organising and offering insight into patterns of meaning (themes) across dataset. The process involves a careful more focussed, re – reading and review of data. Two main reasons to use thematic analysis are its accessibility and flexibility. Nhlonipha theory is tested in this study. Hlonipha can be described as politeness register originating from Nguni and primarily used by Zulu women before and after marriage (Rudwick & Msibi, 2016). The motive behind using this theory is that if you hlonipha you cannot violate another person’s rights but you will have to respect them. The study finds out that men become victims of abuse, and the violation of their rights is just as criminal as the violation of the rights of their female counterparts. This study also inspires harmony and peaceful coexistence among consumers of its content. It is recommended that more studies of similar kind should be undertaken to influence humanity to desist from violating the rights of other human beings. KEYWORDS Man abuse, woman abuse, child abuse, human rights, violation of rights, nhlonipha
Abuse of men's rights in selected Xitsonga drama text
Thesis (Ph.D. (Literature and Philosophy)) --University of Limpopo, 2021
Keywords: Man abuse; Woman abuse; Child abuse; Human rights; Violation of rights; Nhlonipha; Abused men -- Mental health; Psychological child abuse -- Prevention; Ethics; Abused women in literature